2013
DOI: 10.1177/0734371x13506228
|View full text |Cite
|
Sign up to set email alerts
|

Public Agency Hiring, Minimum Qualifications, and Experience

Abstract: Public administrators engage all aspects of a community and need to be skillful in working with elected officials, citizens, business groups, and government employees who make things happen. Minimum qualifications, which act as a primary screening device for applicants and hiring agencies, are based in part on assumptions of the value of education and experience, but those assumptions deserve more consideration given their role in agency staffing. This paper sheds light on the value of hiring new employees wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The employees' perspectives revealed that the odds that the applicants obtain a skilful job are 9.278, 6.672 and 4.888 times higher for those applicants who have work experience, professional certificates and computer skills, respectively, than those applicants who do not have such strengths. These findings are consistent with previous studies (Mulholland and Derdall, 2004; Dougherty and Gelder, 2013; Humburg and Velden, 2015; Farashah et al. , 2018) and with the findings based upon the employers' viewpoint as discussed above in this study.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The employees' perspectives revealed that the odds that the applicants obtain a skilful job are 9.278, 6.672 and 4.888 times higher for those applicants who have work experience, professional certificates and computer skills, respectively, than those applicants who do not have such strengths. These findings are consistent with previous studies (Mulholland and Derdall, 2004; Dougherty and Gelder, 2013; Humburg and Velden, 2015; Farashah et al. , 2018) and with the findings based upon the employers' viewpoint as discussed above in this study.…”
Section: Resultssupporting
confidence: 94%
“…The results showed that the odds that employers hire the employees are 13 times higher for employees who have previous work experience than for employees who do not have any previous work experience. The result about work experience in this study is consistent with the findings of Mulholland and Derdall (2004), Dougherty and Gelder (2013) and Humburg and Velden (2015). Work experience is a core factor in reducing the cost of training, increasing work efficiency and developing work through innovative ideas (Finch et al.…”
Section: Resultssupporting
confidence: 89%
“…Fit studies typically look at employees’ levels of loyalty and commitment (Bhambhri, 1972; Gossett, 2003; Gould-Williams et al, 2014; Jaskyte & Lee, 2009), their intentions to quit (Baker & Jennings, 2000; Gould-Williams et al, 2014; Selden & Sowa, 2015), their job satisfaction (Bhambhri, 1972; Gould-Williams et al, 2014), their competence (Bhambhri, 1972; Hsiung & Hsieh, 2003), and their social integration (Hsiung & Hsieh, 2003), as well as the perceived ambiguity, clarity, or meaningfulness of their roles and goals within the organization (Bright, 2010; Hsiung & Hsieh, 2003; Jaskyte, 2005; Peng, Pandey, & Pandey, 2015). Other fit studies assess the “benefits” of newcomers as perceived by their supervisors (Dougherty & Van Gelder, 2015) or the congruence between the values of an organization and its members (Peng et al, 2015). Finally, Hatmaker and Park (2014) look at newcomers’ networks with their colleagues.…”
Section: Five Streams Of Research On Organizational Socializationmentioning
confidence: 99%
“…Since all federal law enforcement agencies must compete to attract new and experienced recruits to reflect the diversity of the communities they serve, this is certainly a field they will find a pool of qualified candidates. In addition, Dougherty and Van Gelder (2015) found that public servants with prior experience in the public sector have a more balanced approach to decision-making. However, like veteran’s status, state and local law enforcement is also a nontraditional occupation and their percentages are even lower than federal law enforcement—women represent 12.2% of officers in local police departments, 13.9% in sheriffs’ offices, and 6.5% in state agencies (Burch, 2016; Langton, 2010; Reaves, 2015).…”
Section: Recommendations and Discussionmentioning
confidence: 99%